2016
DOI: 10.1136/bmj.i581
|View full text |Cite
|
Sign up to set email alerts
|

Incretin based drugs and the risk of pancreatic cancer: international multicentre cohort study

Abstract: ObjeCtiveTo determine whether the use of incretin based drugs compared with sulfonylureas is associated with an increased risk of incident pancreatic cancer in people with type 2 diabetes.Design Population based cohort.setting Large, international, multicentre study combining the health records from six participating sites in Canada, the United States, and the United Kingdom. Main OutCOMe MeasuresWithin each cohort we conducted nested case-control analyses, where incident cases of pancreatic cancer were match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
118
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(132 citation statements)
references
References 35 publications
10
118
0
4
Order By: Relevance
“…Early observational studies 15,16 suggested that exenatide could be associated with pancreatic cancer; however, a recent study showed no significant associations. 17 Asymptomatic hyperamylasaemia was reported in one patient in the exenatide group, necessitating drug withdrawal. Exenatide can induce amylase secretion in vitro, and increased amylase concentrations have been reported in patients with type 2 diabetes treated with similar drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Early observational studies 15,16 suggested that exenatide could be associated with pancreatic cancer; however, a recent study showed no significant associations. 17 Asymptomatic hyperamylasaemia was reported in one patient in the exenatide group, necessitating drug withdrawal. Exenatide can induce amylase secretion in vitro, and increased amylase concentrations have been reported in patients with type 2 diabetes treated with similar drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in 2,024,441 person-years of follow-up, examination of health records failed to reveal increased reports of pancreatic cancer in individuals treated with incretin-based therapies (77). Given the long latency required for cancer signals to emerge, coupled with the low incidence rates for malignancies such as MTC, it is not yet possible to completely exclude the possibility that a cancer signal might yet emerge in longer, larger studies or following scrutiny of more extensive drug exposure using electronic health databases.…”
Section: Adverse Events Associated With Glp-1r Agonistsmentioning
confidence: 99%
“…Long-term exposure to oxidative stress will lead to intestinal damage, but part of lactic acid bacteria in the intestine can play an antioxidant role, remove free radicals and ease UC [8]. Intestinal mucosa permeability will change as the intestinal tract gradually becomes inflammatory, and the mucous membrane permeability will be greatly improved when inflammation is increased [9,10]. Study has shown that some lactic acid bacteria can alleviate DSS-induced colitis by improving the permeability of intestinal mucosa [11].…”
Section: Biomedical Research 2018; 29 (4): 768-774mentioning
confidence: 99%